Sheath Blight and Bacterial Blight Resistance in Rice: Mechanisms, Progress and Future Perspectives for Sustainable Rice Production (Plant Bulletin, 2024)
Rice (Oryza sativa L.) is a staple food for nearly half of the world's population, including Pakistan. But several diseases are always posing a threat to rice farming, with bacterial blight and sheath blight being the two most common causes. R. solani is the main source of rice sheath blight and stood crop’s most destructive diseases. Reviewing published data on pathogenicity and disease management is crucial to developing effective crop protection against sheath blight. It also helps identify research gaps that need more in-depth investigation. Although there has been progress in identifying rice and pathogen-related genes linked to pathogenesis, the underlying processes are still unknown. Research on the applications of; agronomic techniques, chemical control, biological control, and genetic improvement in disease management strategies has been conducted. Optimizing the application of nitrogen fertilizer in combination to plant-plant spacing can minimize the transmission of infection, whereas SMART agricultural technologies; like crop monitoring using Unmanned Aerial Systems help detect and treat sheath blight disease early on. Biological agents and natural fungicides can be used to effectively prevent sheath blight while reducing the negative effects on the environment. Genetic strategies that hold potential to control sheath blight include the use of exogenous dsRNA to suppress pathogen gene expression, genome editing to create rice lines less susceptible to sheath blight, and the development of transgenic rice lines that over express or silence genes related to pathogenesis. The pathogen’s flexibility, the absence of resistant rice types, the lack of single resistance genes for breeding, and farmers' restricted access to informative programs about optimum management methods all work against effective crop protection against sheath blight.
Keywords: sheath blight; susceptible disease; conventional approach; transgenic; molecular tools